Economic Resilience as a Component of National Defense: Formulation of Strategies to defend against Non-Conventional Threats - Pratiwi, Ire; Asep Adang Supriyadi; Yosef Prihanto (International Journal of Education, Vocational and Social Science, 2026)
Economic resilience is analyzed as an integral component of national defense in the defense of unconventional threats such as economic wars, cyberattacks, and geopolitical pressures. The capacity of states to defend sovereignty, adapt to change, and mitigate the impact of external attacks that disrupt social and political stability is the focus of this study. The relationship between economic resilience, fiscal policy, diversification of economic sectors, and strengthening technological infrastructure, including cyber defense, is highlighted as interrelated elements to maintain economic stability and national security. This study examines adaptive response and policy strategies, including intersectoral collaboration and international cooperation, to anticipate the complex dynamics of global economic threats. The findings indicate that the synergy of planned economic policies with a comprehensive defense strategy can strengthen national capabilities to respond to non-military threats, maintain internal stability, and improve the country's geopolitical position.